LOGISTICS AND MARKETING SUPPORT IMPROVEMENT IN THE EXPORT SUPPLY CHAIN (INNOVATIVE ECONOMY, 2021)
Polishchuk I.I., Dovhan Yu.V., Korol I.V. LOGISTICS AND MARKETING SUPPORT IMPROVEMENT IN THE EXPORT SUPPLY CHAINPurpose. The purpose of the article is to clarification of approaches to the improvement of logistics and marketing support of managing the oil and fat export supply chain.Methodology of research. Theoretical and methodological basis of the study has been formed by the scientific works of domestic and foreign scientists in the field of logistics and marketing (to identify scientific approaches to marketing and logistics management of export supply chain management), methods of critical, systematic and comparative analysis (to analyze the features of marketing and logistics management of export oil and fat supply chain), methods of graphical analysis (to clearly display the research results), as well as the abstract and logical method (for the logical generalization of theoretical principles and formulation of research conclusions).Findings. It has been formed that the global situation in the oil and fat market, consumer preferences and tastes in the world are changing dynamically and pose new challenges to companies that can be addressed by gaining more sustainable competitive advantages than those already gained due to the marketing- and logistics-oriented approaches to business activity. It is determined that logistics and marketing are defined as the main orientations of management in a company and interpreted in the real sense as significant spheres of functional and integrated processes in company, and in a modern company marketing must be logistic, logistics must be a marketing one.It is established that a key position in the export supply chain of oil and fat products is occupied by the consumer. It is proved that one of the possible directions of effective consideration of market challenges is the logistization of the marketing activity of oil and fat enterprises and the use of integrated marketing logistics.It is substantiated that formation of sustainable competitive advantages of oil and fat companies in the global supply chains is possible due to the development of marketing-mix that will include marketing and logistics components.Originality. Theoretical and methodological principles have been deepened and of scientific and applied recommendations for improving the logistics and marketing support of export supply chain management have been developed. In particular, a logistics scheme for the export chain of oil and fat supply has been developed, which, in contrast to the existing ones, involves the use of river transport, which will reduce logistics costs, improve logistics services and increase customer satisfaction.Practical value. The results of the study can be implemented in the practice of managing export supply chains of domestic enterprises, which will increase the efficiency of export activities by reducing logistics costs, improving the level of logistics services and increasing the degree of customer satisfaction.Key words: logistics support, marketing support, export, supply chain, oil and fat.
Keywords: Key words; logistics support; marketing support; export; supply chain; oil and fat.